$e$ is the identity of the group.

My understanding: To prove that $b^{33}=e$ is the same as proving $b^{34}=b$

Now, $a * b^4 * a=b^7$

$\Rightarrow b^4= a*b^7*a=(a*b*a)^7$

This is how far I went. I'm stuck here. Please help.


For any integer $n$ we have $$(ab^4a)^n=b^{7n}$$ or $$ab^{4n}a=b^{7n}$$ For $n=4$, $$ab^{16}a=b^{28}$$ and for $n=7$, $$ab^{28}a=b^{49}$$ Therefore $$b^{16}=b^{49}$$

EDIT: With same technique, it can be shown that if $a^2=e$ and $ab^r=b^sa$ then $b^{r^2}=b^{s^2}$.

  • $\begingroup$ Another solution: Note that $a$ and $b^{11}$ commute; then take $n=11$ above to get $b^{44}=b^{77}$. $\endgroup$ – Aravind Jul 14 '15 at 9:27
  • $\begingroup$ @ajotatxe Nice ... Vote up! $\endgroup$ – johannesvalks Jul 14 '15 at 9:29
  • $\begingroup$ Very nice, +1 Then one could note that in the dihedral group of order $66$, generated by an element $c$ of order $33$, and by an element $a$ of order $2$, one has $c a c = c^{-1}$, and for $b = c^{3}$, one has $a b^4 a = a c^{12} a = c^{-12} = c^{21} = (c^{3})^{7}= b^7$. So $b^{33} = 1$ is the best we can squeeze out of the relations. $\endgroup$ – Andreas Caranti Jul 14 '15 at 17:09

Note that \begin{align} (aba^{-1})^4&=b^7\text{, and }\\ b^4&=(aba^{-1})^7\nonumber\\ (aba^{-1})^7&=b^4. \text{So 'dividing' the first equality by the last,}\\ (aba^{-1})^{-3}&=b^{3}. \text{ Multiplying it with the first equality,}\\ aba^{-1}&=b^{10}\\ (aba^{-1})^4&=b^{40}=b^7\\ \text{So }b^{33}&=e \end{align}


$\textbf{Different approach:}$

$ab^4a=b^7$ and $ab^7a=b^4$. So $$b^{11}=b^4b^7=ab^{11}a$$ Hence, $$(b^4)^{11}=(ab^7a)^{11}=ab^{77}a=(b^{11})^4=(ab^{11}a)^4=ab^{44}a$$. Hence, $$b^{44}=b^{77}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.